La Bible au Congrès. Pentecôtisme et politique au Brésil (1986-2016) - Richard Marin (Caravelle)
In Brazil, in less than three decades, the Pentecostals have become one of the main actors of national politics. Like in several other countries of Latin America, this has largely contributed to the reorganization of the religious field which was done in favor of Pentecostals. How is it possible to explain the increasing number of their congregants ? The reasons for their electoral triumphs ? Could they become a threat for democracy, as it has been often mentionned ? So many questions that this paper will try to answer.